Ensino e aprendizagem na educação física escolar para alunos com Transtorno do Déficit de Atenção e Hiperatividade (TDAH): desafios e possibilidades pedagógicas - Tôsto, Luana Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This bibliographic research aimed to highlight how school Physical Education is established as a formative pedagogical practice in the cognitive, socio-affective, and behavioral development of children with Attention Deficit Hyperactivity Disorder (ADHD). Publications from 2015 to 2025 were analyzed, addressing Physical Education as a field of knowledge capable of integrating body, movement, and learning in the student’s holistic formation. The analysis revealed that movement, when pedagogically mediated, goes beyond expressive dimensions and consolidates itself as a language for constructing attention, self-regulation, and belonging. Body practices guided by educational intentionality foster the development of cognitive, emotional, and social competencies, strengthening bonds and enabling students with ADHD to be recognized in their uniqueness. Furthermore, it was found that the Physical Education teacher, acting as a sensitive mediator and qualified observer, plays a structuring role in organizing learning environments that embrace the diversity of children’s behavior. Therefore, Physical Education, by uniting body, movement, and pedagogy, reaffirms itself as an essential formative practice in building a more inclusive, human, and sensitive school.

Esta pesquisa bibliográfica teve como objetivo evidenciar como a Educação Física escolar se constitui como prática pedagógica formadora no desenvolvimento cognitivo, socioafetivo e comportamental de crianças com Transtorno de Déficit de Atenção e Hiperatividade (TDAH). Foram analisadas produções publicadas entre 2015 e 2025 que compreendem a Educação Física como campo de conhecimento capaz de integrar corpo, movimento e aprendizagem na formação integral do estudante. A análise das obras revelou que o movimento, quando mediado pedagogicamente, ultrapassa a dimensão expressiva e se consolida como linguagem de construção da atenção, da autorregulação e do pertencimento. As práticas corporais orientadas por intencionalidade educativa favorecem o desenvolvimento de competências cognitivas, emocionais e sociais, fortalecendo vínculos e possibilitando que o aluno com TDAH seja reconhecido em sua singularidade. Ainda, verificou-se que o professor de Educação Física, ao atuar como mediador sensível e observador qualificado, tem papel estruturante na organização de ambientes de aprendizagem que acolhem a diversidade do comportamento infantil. Portanto, a Educação Física, ao unir corpo, movimento e pedagogia, reafirma-se como prática formativa essencial na construção de uma escola mais inclusiva, humana e sensível às diferenças.
Teaching and learning in physical education for students with Attention Deficit Hyperactivity Disorder (ADHD): challenges and pedagogical possibilities
Keywords: Educação Física escolar; TDAH; Ensino e aprendizagem; Inclusão escolar; Mediação pedagógica; School Physical Education; ADHD; Teaching and learning; School inclusion; Pedagogical mediation